PENEGAKAN HUKUM TERHADAP KENDARAAN BERMOTOR ANGKUTAN BARANG MENGENAI TATA CARA PEMUATAN DAYA ANGKUT DAN DIMENSI KENDARAAN BERDASARKAN UNDANG- UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KOTA PEKANBARU - Muhammad Fadil Abdillah; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The presence of large-dimensional vehicles and large capacity is a factor causing road damage and high fasalitas for road users in Pekanbaru City. The obligation to comply with the provisions of goods shall be regulated in Article 169 paragraph (1) of Law Number 22 Year 2009 regarding LLAJ which reads "The Driver and / or Public Transport Company must comply with the provisions on loading procedures, transportation capacity, vehicle dimension and road class, large tonnage in violation of the hauling procedure is very disturbing to the public.The rise of violation of cargo goods that occurred in Pekanbaru City is not free from the law enforcement process that has not been optimal, therefore the law enforcement of motor vehicle goods that are not in accordance with the provisions must be optimized to realize legal certainty and public comfort.The purpose of writing this thesis, namely: First, To know the law enforcement of vehicle freight knowing the procedure of loading and transporting vehicle dimensions based on Law no. 22 Year 2009 About LLAJ in Pekanbaru City. Second, To know the obstacles in law enforcement of motor vehicle freight in general. Third, To know the efforts made in the law enforcement of motor vehicle freight in general.This type of research can be categorized in the type of sociological research. The research location is Pekanbaru City. Sources of data used are primary data and secondary data. Data collection techniques are interviews and literature study using deductive methods that draw conclusions from things that are general to things that are special.From the research results can be concluded. First, the enforcement of motor vehicle law in Pekanbaru City has not been proven optimally with high freight cost. Secondly, lack of optimization of law enforcement caused by obstacles such as limited authority of PPNS Dinas Perhubungan, lack of regulations on limitation of freight rates, corruption, lack of coordination of authorized institutions, minimal facilities and facilities, absence of storage warehouse, lack of awareness of drivers and cultural factors. Third, motor vehicle law enforcement efforts in Pekanbaru City include the stipulation of regulation concerning limitation of public transportation tariff and strengthening of authority of Transportation Department Vehicle, personnel skill improvement, budget improvement for provision of weighing tool and improvement of facilities and socialization and law enforcement to increase awareness about traffic safety .Keywords: Law Enforcement-Motor Vehicle Transportatio-Procedures for Vehicle Resilience and Dimensions of Motor Vehicle Law No 22 Year 2009 About LLAJ-Pekanbaru City